Fungal Nail Infections in Tehran, Iran - F Zaini; M Mahmoudi; ASA Mehbod; P Kordbacheh; M Safara (Tehran University of Medical Sciences, 2009)
"nBackground: Onychomycosis results from invasion of the nail plate by dermatophytes, yeasts or mould species of fungi. The objective was to determine the etiological agents of onychomycosis."nMethods: A total of 549 patients clinically suspected of onychomycosis were examined for causative fungal agents. Both direct microscopy and the cultures of the nail material were performed to identify the causative agents between 2004-2005 in Tehran, Iran."nResults: Out of 549 cases examined, 263(47.9%) were mycologically proven cases of onychomycosis (139 finger, 124 toe nails), among those 33(6.09%) were only positive in direct microscopic examination. From an etiological point of view, 21.85% of nail infections were caused by yeasts, 10.55% were infected by dermatophytes and 15.5% by non-dermatopyte moulds. Candida albicans was the common yeast causative agent (16.73%) followed by A. flavus (11.78%), T. mentagrophytes (10.26%), C. parapilosis (9.12%), C. tropicalis (8.74%), A. fumigatus (6.08%), T. rubrum (4.94%), A. niger (3.04%), Penicillium spp. (2.66%), Aspergillus spp (1.90%), each of Rhizopus spp and Cladosporium spp (1.52%), C. guilliermondii (1.14%), Scopolariopsis spp. (1.14%), each of C. famata, C. glabrata, C. krusei, S. lusitania, Acremonium spp. (0.76%) and C. homicola (0.38%), T. rubrum (4.94%). Candida species were most common responsible agent for onychomycosis in female hands (74.1%) followed by 17.26% non-dermatophyte moulds. Dermatophytes caused tinea unguim of hand (8.63%) and peduum (37.1%) in males. Onychomycosis of finger nails was most prevalent in females while toenail infection was common in male patients."nConclusion: The yeasts of the Genus Candida and non-dermatophyte moulds are dominant cause of female finger nail onychomycosis and dermathophytes are principal cause of both finger and toe nails in males in Tehran.